2013
DOI: 10.1016/j.psyneuen.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of early poverty on cortisol in young children: Moderation by autonomic nervous system activity

Abstract: The relation of the cumulative experience of poverty in infancy and early childhood to child cortisol at age 48 months was examined in a prospective longitudinal sample of children and families (N=1,292) in predominantly low-income and rural communities in two distinct regions of the United States. Families were seen in the home for data collection and cumulative experience of poverty was indexed by parent reported income-to-need ratio and household chaos measures collected between child ages 2mos and 48mos. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 52 publications
6
47
0
3
Order By: Relevance
“…These results are consistent with studies showing blunted physiologic stress responses among low-SES children (Blair, Berry, Mills-koonce, Granger, & The FLP Investigators, 2013; Evans & Kim, 2007). SES-related differences in cortisol likely reflect a combination of psychosocial and environmental effects.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with studies showing blunted physiologic stress responses among low-SES children (Blair, Berry, Mills-koonce, Granger, & The FLP Investigators, 2013; Evans & Kim, 2007). SES-related differences in cortisol likely reflect a combination of psychosocial and environmental effects.…”
Section: Discussionsupporting
confidence: 92%
“…Prior research suggests that early life stressors compound the effects of prenatal stressors by chronically over-activating physiological systems such as the HPA axis, eventually leading to down-regulation of the response until an individual demonstrates a blunted response [1016]. Two recent studies found that the effects of poverty, financial instability, and caregiver instability accumulated over time resulting in a decline in cortisol [14] and time in poverty along with household chaos were associated with a flattened cortisol change trajectory [16]. PDE is often associated with multiple stressors such as non-supportive or absent caregivers, few financial resources, neighborhood and/or home violence exposure, continued caregiver drug use, multiple out-of-home placements, and increased likelihood of various forms of abuse [46].…”
Section: Discussionmentioning
confidence: 99%
“…These disruptions may prevent an expected stress response, resulting in a blunted cortisol or atypical response to stress over time [10,11]. This process has been demonstrated in maltreated and deprived/neglected children [1013] and in children with early life stress (e.g., harsh parenting, poverty) [1416]. …”
mentioning
confidence: 99%
“…SED is associated with elevated baseline levels of cortisol during childhood (Essex et al 2002;Evans and English 2002;Flinn and England 1997;Gustafsson et al 2006;Lupien et al 2001;Lupien et al 2000) and adolescence although Lupien et al (2001) found that by age 12, SES is no longer related to baseline cortisol levels. The longer children experience poverty, the higher the cortisol level (Blair et al 2013). In a particularly noteworthy study, Chen et al (2010) examined salivary cortisol every 6 months for a 2-year period among a group of adolescents.…”
Section: Physiological Systemsmentioning
confidence: 99%